Analisis Pola Konsumsi Masyarakat Kota Batam Berdasarkan Penggunaan E-Money Berbasis Aplikasi - Wan Maharani S.S; Arif Darmawan (Politeknik Negeri Batam, 2020)
This study aims to analyze the use of application-based e-money in the people of Batam City and how people's consumption patterns with the use of e-money. The population in this study is the people of Batam City with judgment sampling techniques, so that the sample obtained as many as 318 respondents. The data analysis technique used is descriptive-quantitative analysis. The results showed that the e-money application that was most widely used by the people of Batam was Dana. Furthermore it is known that expenditure for consumption of both food and non-food using application-based e-money in Batam City is still relatively low and there is a slight shift in consumption patterns in the community, which is the most expenditure occurs in the entertainment consumption group.